An optimal beam alignment method for large-scale distributed space surveillance radar system. Issue 11 (1st June 2018) - Huang, Jian; Wang, Dongya; Xia, Shuangzhi
Highlights: A two dimensional beam projection method is proposed using the direction angles. The optimal orientation angle of the antenna array is precisely solved. The site location can be optimally fixed to realize the optimal beam alignment. The beam pointing direction can be calculated for the optimal T/R beam coverage. The beam alignment method is proved effective using the real parameters of AFSSS. Abstract: Large-scale distributed space surveillance radar is a very important ground-based equipment to maintain a complete catalogue for Low Earth Orbit (LEO) space debris. However, due to the thousands of kilometers distance between each sites of the distributed radar system, how to optimally implement the Transmitting/Receiving (T/R) beams alignment in a great space using the narrow beam, which proposed a special and considerable technical challenge in the space surveillance area. According to the common coordinate transformation model and the radar beam space model, we presented a two dimensional projection algorithm for T/R beam using the direction angles, which could visually describe and assess the beam alignment performance. Subsequently, the optimal mathematical models for the orientation angle of the antenna array, the site location and the T/R beam coverage are constructed, and also the beam alignment parameters are precisely solved. At last, we conducted the optimal beam alignment experiments base on the site parameters of Air Force Space Surveillance System (AFSSS). The simulation results demonstrate the correctness and effectiveness of our novel method, which can significantly stimulate the construction for the LEO space debris surveillance equipment.